Changing of expression actinbinding proteins in the kidney under dehydration - I. I. Khegay (Вавиловский журнал генетики и селекции)
Actin is related to main structural proteins in eukaryotes. In opposite to muscle alpha-actin, beta-actin is expressing in all types of cells. The constant reorganization of actin cytoskeleton takes place in non-muscle cells. Fibrillar actin, organized by globular monomers, interacts with the actin-binding proteins. Alpha-actinin forms a transverse links in actin fibrillar network, as well as concentrates in the fields of focal contacts. Tropomyosin is related to regulatory components of beta-actin, and due to the expense of longitudinal localization of the molecule in the groove of actin microfilament, stereochemically shields the sites of other actin-binding proteins. The most important function of actin cytoskeleton is the participation in the transportation of vesicles with aquaporins of second type in principal cells of an epithelium of collecting ducts in renal medulla. Vasopressin is stimulating the release of aquaporin tetramers from cytoplasmic store to apical plasmatic membrane. The participation and role of separate cytoskeleton proteins in the process of aquaporin trafficking and forming additional pores for water stays a poorly studied place in the molecular physiology of kidney. We explored the osmoregulatory action of prolonged hydration and dehydration on the protein composition of actin cytoskeleton in rats depending on the presence or absence of the actively expressing vasopressin gene in the genome. We found that the efficiency of the renal concentrating system, controlled by vasopressin, depends on expression of actin-binding proteins in the renal medulla. On the background of a stable level of inner cellular beta-actin, a change of expression an alpha-actinin and tropomyosin is observed. Dehydration of the organism is accompanied by essential reducing of alpha-actinin. In the absence of vasopressin, reduction of alpha-actinin has a smaller amplitude. The presence of the normal vasopressin gene in the genome, regardless of transitory expression level and secretion of hormone, is a factor of lower tropomyosin in the kidney. The most probable molecular mechanism of changing the expression of the genes for alpha-actinin and tropomyosin is transduction of the V2-mediated vasopressin hormonal signal to protein kinase A, phosphorylation of the cAMPresponsible transcriptional factor CREB, and nuclear CREB interaction with gene CRE sites sensitive to it.